2010
DOI: 10.1140/epjb/e2010-00185-3
|View full text |Cite
|
Sign up to set email alerts
|

Biased diffusion in a piecewise linear random potential

Abstract: We study the biased diffusion of particles moving in one direction under the action of a constant force in the presence of a piecewise linear random potential. Using the overdamped equation of motion, we represent the first and second moments of the particle position as inverse Laplace transforms. By applying to these transforms the ordinary and the modified Tauberian theorem, we determine the short-and longtime behavior of the mean-square displacement of particles. Our results show that while at short times t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
(51 reference statements)
0
18
0
Order By: Relevance
“…Such an analysis has recently been presented for the case of a piecewise linear random potential [22], but seems not yet to be available for the more realistic potentials considered here.…”
Section: Resultsmentioning
confidence: 99%
“…Such an analysis has recently been presented for the case of a piecewise linear random potential [22], but seems not yet to be available for the more realistic potentials considered here.…”
Section: Resultsmentioning
confidence: 99%
“…The particle returning to a lattice point visited already, "remembers" its waiting time there. Mathematicians have rigorously shown that in dimensions higher than one [28] or in the presence of a bias [55] (see also [56][57][58]) the CTRW approach describes well the quenched dynamics since the particle does not tend to revisit the same lattice points many times, thus confirming physical insight in [16,17,26] (for dimension d = 2 logarithmic corrections are also important). While the three dimensional QTM belongs to the domain of attraction of the CTRW the calculation of the anomalous diffusion constant is not trivial (see discussion in the summary).…”
Section: Subordination In the Annealed Trap Model (=Ctrw)mentioning
confidence: 99%
“…Clearly this situation can occur in the case in which the external forcing F 0 is exactly the critical tilt, as it was pointed out in Ref. [8,9].…”
Section: B Unbounded Crossing Times With Fast Decay Of Correlationsmentioning
confidence: 55%
“…A more recent approach to the problem of deterministic diffusion of overdamped particles in disordered potentials was carried by S. I. Denisov et al in Ref. [9]. They consider a class of piece-wise linear random potentials and this simplification let them find analytical expression for the diffusion coefficient (when normal diffusion occurs) as well as for the long-time and the short time behavior of the mean square displacement.…”
Section: Introductionmentioning
confidence: 99%